A Master-Slave Operating Technique for Material Removal Processes - Arayavongkul, R.; Sangveraphunsiri, V. (Applied Science and Engineering Progress, 2013)
This paper presents a master-slave operating technique for the material removal process aimed to be used for part prototyping. This system is designed for 5-axis milling processes which consist of a 6-DOF parallel haptic device as a master arm and a hybrid 5-axis H4 family parallel manipulator as a slave. According to the dissimilar structures between the master and slave, an operating technique to define positions and orientations of the slave’s end effecter or milling tool is applied in Cartesian space. Force reflection techniques in this work can help the operator move the master arm’s handle firmly along the virtual wall and generate significant feeling of force in master-slave milling tasks. The results of ball-end milling tasks show that each reproduced wooden work piece is similar to its referenced object with an average error of about 1 mm on each side and this master-slave operating technique can be used for dimensional scaling tasks.